Quality of Life of Post-Gastrectomy Patients: A Study in Indonesia's National Central Hospital - Napitupulu, Herlan; Putranto, Agi S (The New Ropanasuri Journal of Surgery, 2021)
Introduction. Several studies suggest gastrectomy is associated with deterioration in a patient's quality of life (QOL). This study is conducted to assess the impact of distal (DG), proximal (PG), or total (TG) gastrectomy and the cause of disease on a patient's QOL. Method. This retrospective study was conducted in dr. Cipto Mangunkusumo Hospital with collected data from the medical records throughout July-September 2020. Inclusion criteria were patients after proximal, distal, or total gastrectomy for a tumor or any non-tumor indications. They were assessed using the World Health Organization Quality of Life Questionnaire Abbreviated Version (WHOQOL-BREF). Collected data were further analyzed using statistical univariate and bivariate analysis. Results. Sixty-six patients with a mean age of 47.12 ± 14.5 years were enrolled in the study. We found significant differences between the proximal, distal, and whole groups with the environmental domain and the total WHOQOL-BREF values. The median scores for the environmental domain were 63 (50–88), 69 (50–88), 56 (50–75), and the mean WHOQOL-BREF total scores for proximal, distal, and total gastrectomy patients were 64.42 ± 9.34, 67.19 ± 9.44, 59.12 ± 8.04 for the proximal, distal, and total groups, respectively. Subjects with an etiology of malignancy had a lower median WHOQOL-BREF score in most domains. However, there was no significant difference in WHOQOL-BREF scores between non-tumor and tumor subjects. Conclusion. This study found decreasing patients' QOL after total gastrectomy compared with distal and proximal in the environmental domain and the total WHOQOL-BREF value. There was no difference in post-gastrectomy patients' QOL between tumor and non-tumor etiology in all WHOQOL-BREF domains.